Gender and Social Behavior of Tiktok Users: Necessity, Polularity or Lifestyle? - Anis Mirna Defi; Achmad Hufad (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
The emergence of TikTok has been a highlight for the global community. This short video application with a variety of interesting features can penetrate the lives of various groups. Many people use TikTok as a means of entertainment, seeking knowledge to achieve popularity. The purpose of this study is to describe the role of gender in the selection of TikTok video content and determine the influence of gender on the social behavior of TikTok users. Descriptive quantitative was chosen as the research approach and data collection used a questionnaire. Validity and reliability tests were conducted on 15 questions with Gender as the independent variable and social behavior as the dependent variable. The overall sample size was 192 respondents, consisting of 139 women and 53 men selected by convenience sampling. The research findings show that 80.2% of respondents tend to choose lipsync or dance content played by women, while the remaining 19.8% choose men. Social behavior in TikTok users is mostly aimed at content selection, while there is no significant influence in the category of actions taken by users after viewing TikTok videos.